Diagnosis of death using neurological criteria in adult patients on extracorporeal membrane oxygenation: Development of UK guidance. (February 2020) - Meadows, CIS; Toolan, M; Slack, A; Newman, S; Ostermann, M; Camporota, L; Gardiner, D; Webb, S; Barker, J; Vuylsteke, A; Harvey, C; Ledot, S; et al.
The diagnosis of death using neurological criteria is an important legal method of establishing death in the UK. The safety of the diagnosis lies in the exclusion of conditions which may mask the diagnosis and the testing of the fundamental reflexes of the brainstem including the apnoea reflex. Extracorporeal membrane oxygenation for cardiac or respiratory support can impact upon these tests, both through drug sequestration in the circuit and also through the ability to undertake the apnoea test. Until recently, there has been no nationally accepted guidance regarding the conduct of the tests to undertake the diagnosis of death using neurological criteria for a patient on extracorporeal membrane oxygenation. This article considers both the background to and the process of guideline development.